CONTEMPORARY PERSPECTIVES ON THE LINGUISTIC CONCEPTUALIZATION OF REALITY - Karimova Go’zal Ixtiyorovna (International Journal of Literature and Language Studies, 2026)
Within contemporary linguistic scholarship, the notion of concept has emerged as a key object of investigation. Concepts function as fundamental cognitive units that structure human knowledge and shape the perception of reality. Through language, speakers not only represent the external world but also convey the outcomes of their intellectual, cultural, and social experiences. Therefore, the analysis of concepts and linguistic worldviews constitutes a major direction in cognitive linguistics, which focuses on understanding the relationship between language, thought, and cultural consciousness.